Islamic Philosophy: Analytical Study of Figures and Their Thoughts - Ismi Ulfi Aoliyah; Didik Himmawan; Siti Nurjana; Luvia Hanum (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2024)
Islamic philosophy is a branch of philosophy that is closely related to Islamic teachings. This philosophy not only links human thinking with life, but also with the spiritual context of the Islamic religion. Islamic philosophy did not completely originate from Greek philosophy, but was also born from the teachings of Muslim philosophers in the Middle East. The purpose of this research is to find out analytical studies about figures and their thoughts. The research method used in this research is a qualitative method with a literature study approach, in the technique of reviewing and concluding various literature sources that are relevant to the topic under study. The results of this research are that Alkindi's philosophical thinking is focused on Al-Kindi being known as the "first Arab philosopher" and contributing a lot in integrating Greek philosophy with Islamic thought. The result of this research is that Al-Farabi's thoughts are known as the "Second Teacher" after Aristotle and played an important role in developing political philosophy and Islamic ethics. He believed in the importance of wisdom and reason in achieving ultimate happiness. The results of the research are that Ibn Sina's thoughts are one of the greatest figures in medicine and philosophy. His work "The Canon of Medicine" became a standard text in European universities for centuries. The results of the research are the thoughts of Al-Ghazali who was a famous theologian, philosopher and Sufi. He is often credited with opposing the extreme rationalism of earlier philosophers such as Ibn Sina and Al-Farabi. In his work "Tahafut al-Falasifah" (The Collapse of the Philosophers), he criticized philosophers for their views which were considered contrary to Islam. The results of the research are that Ibn Khaldun is a historian and sociologist who is known for his work "Muqaddimah" which is one of the first analyzes of history, society and economics.